Early Integration of Palliative Care for Children with High‐Risk Cancer and Their Families. Issue 4 (18th November 2015) - Kaye, Erica C.; Friebert, Sarah; Baker, Justin N.
Abstract : Despite increasing data to support pediatric palliative care (PPC) as an integral component of high‐quality care for children with life‐threatening conditions and their families, timely integration of PPC is offered inconsistently to children with high‐risk cancer. In this review, we summarize the growing body of literature in support of early integration of PPC for children with high‐risk cancer and their families, advocating that PPC principles and resources are imperative to holistic cancer‐directed care and rooted in evidence‐based medicine. Finally, we offer possible strategies for optimizing integration of PPC into holistic cancer care for children and families.